2018
DOI: 10.13189/ujcm.2018.060101
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship between Breast Cancers ‎and HPVs

Abstract: High-risk human papillomaviruses (HR-HPVs) have been implicated in the aetiology of a variety of human cancers, including cervical, colorectal, and head and neck (HN); also, (HPVs) may be important risk factors for breast carcinogenesis and metastasis. Previous studies that evaluated the prevalence of HPVs in breast cancer have generated considerable controversy. Based on this hypothesis, we aimed to investigate the prevalence of HPV infection in invasive breast cancer tissues. Our study included 80 paraffin b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…For the first time in 1992, Di Lonardo A and colleagues suggested that HPV could play a crucial role in the genesis of breast carcinoma by detecting HPV16 DNA sequence in 29.4% of breast and lymph node samples [ 28 ]. Following the first publication, several more studies have documented the presence of HPV in malignant breast tumors [ 29 – 31 ]. On the contrary negative relationship between HPV and breast cancer has been declared by a few studies [ 32 – 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the first time in 1992, Di Lonardo A and colleagues suggested that HPV could play a crucial role in the genesis of breast carcinoma by detecting HPV16 DNA sequence in 29.4% of breast and lymph node samples [ 28 ]. Following the first publication, several more studies have documented the presence of HPV in malignant breast tumors [ 29 – 31 ]. On the contrary negative relationship between HPV and breast cancer has been declared by a few studies [ 32 – 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the rst time in 1992 Di Lonardo A and colleagues suggested that HPV could play a crucial role in the genesis of breast carcinoma by detecting HPV16 DNA sequence in 29.4% of breast and lymph node samples (28). Following the rst publication, several more studies have documented the presence of HPV in malignant breast tumors (29)(30)(31). On the contrary negative relationship between HPV and breast cancer has been declared by few studies (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…For the rst time in 1992 Di Lonardo A and colleagues suggested that HPV could play a crucial role in the genesis of breast carcinoma by detecting HPV16 DNA sequence in 29.4% of breast and lymph node samples (28). Following the rst study, several studies have shown the presence of HPV in malignant breast tumors (29)(30)(31). Conversely, con icting studies were declared the negative relationship between HPV and breast cancer (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%